Etude comparative des différents paramètres lipidiques chez les diabétiques de type 1 et 2 et enquête ethnobotanique des plantes médicinales antidiabétiques dans l’ouest Algérien. - GUENDOUZ, Asmaa; HAMZA ZERIGAT, Imane (My University, 2018)
Lipid abnormalities play an important role in increasing the cardiovascular risk of diabetic patients. They are essentially characterized by an increase in triglycerides and a drop in HDL cholesterol, but also by qualitative and kinetic anomalies affecting all lipoproteins (VLDL, LDL and HDL). The objective of our work is to carry out a comparative study of lipid parameters (cholesterol, HDL-C, LDL-C, triglycerides) in diabetic patients consulting at the laboratory of biochemistry in house diabetic (EPSP) salamander and an ethnobotanical study of the antidiabetic plants of the wilaya of Mostaganem and port to the chicken. To establish a catalog of medicinal plants for valorization for the subsequent production of improved traditional medicines. According to our first study, our results showed that blood glucose values in type 1 diabetes showed a significant increase in both sexes compared to type 2 diabetics, the HDL-C values did not show a significant difference in both patients. equality. Cholesterol and LDL-C values in type 1 diabetes show a significant increase in both sexes compared to type 2 diabetics, while triglyceride means show a significant increase in type 2 diabetes compared to type 1 diabetics. Regarding the ethnobotanical study the most used plants are white mugwort, Incense, Fenugreek, Cinnamon and Oregano. The foliage is the most used part of the plant while the infusion is the most used instructions in the phytotherapeutic treatment. In light of this study, we would like to sensitize the local population about the risks and dangers of the anarchic use of plants for phythotherapeutic use, in particular, the use of hypoglycemic plants that are toxic
Keywords: diabète; glycémie; cholestérol; HDL; LDL; triglycéride; l’armoise blanche; Encens; Fenugrec; Cannelier; l’origan; ethnobotanique; médecine traditionnelle; diabetes; blood sugar; cholesterol; triglyceride; white mugwort; incense; fenugreek; cinnamon; oregano; ethnobotany; traditional medicine.